Financial Dollarization : The Policy Agenda - Armas, Adrian (International Monetary Fund, 2006)
Financial (unofficial) dollarization is widely seen as a critical source of financial fragility in both developing and emerging economies. This volume provides a rigorous and balanced perspective on the causes and implications of dollarization, and the basic policies and options to deal with it: the adaptation of the monetary and prudential frameworks, the development of local-currency substitutes, and the scope for limiting dollarization through administrative restrictions. For more information on how to purchase a copy of this title, please visit http://www.palgrave.com/economics/imf/index.asp.